Lesbian Relationship in Shobha De’s Strange Obsession: Exploring Boldness and Openness in Shobha De's Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2021)
With the publication of her first novel Socialite Evenings (1889), the best seller, Shobha De took the literary world by storm and invited both unqualified applause and strong denunciation by the critics. Succeeding novels appeared one by one rapidly in a decade and established her as one of the mainstream women writers in India owing to her profound writing skills and her extra ordinary gift to discuss every sensitive aspect in her fiction. Even while writing on sex, she feels no hesitation and is not stopped by social sanctions. She does not think sex as a matter of shame or an activity to be concealed. She differs considerably from other Indian women novelists for her boldness, openness and frankness. Her bold and modern approach has made her famous the world over.